Overview of the Application and Research of the Classic Formula Shenghua Decoction in the Field of Gynecology - Yang, Zuoyi; Hou, Xue; Cui, Xiaoping; Cui, Panjie (Journal of Contemporary Medical Practice, 2025)
Shenghua Decoction originates from “Fu Qingzhu’s Gynecology” by Fu Shan of the Qing Dynasty. Its main effects are promoting blood circulation to remove blood stasis, and warming the meridians to relieve pain. The original formula was indicated for persistent lochia due to blood deficiency and cold invasion after childbirth. It is now extensively applied in treating various gynecological diseases, such as menstrual disorders, postpartum diseases, miscellaneous diseases, and pregnancy-related disorders. Its therapeutic effect is significant and has gained widespread recognition. In recent years, with the development of Traditional Chinese Medicine and scientific technology, the clinical efficacy and pharmacological research on Shenghua Decoction have become a focus of scholarly attention. This article will summarize the application of Shenghua Decoction in gynecology from two aspects: its current application status and its mechanism of action. The aim is to explore the application and research progress of Shenghua Decoction, derive important information, thereby enabling it to better serve clinical practice and scientific research, and be more beneficial for patient treatment.